Фітотехнологічні засади боротьби з алелопатичною ґрунтовтомою у монокультурних насадженнях Syringa vulgaris L. - Pavliuchenko, N.A.; Dovhaliuk, N.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – to analyze the effect of brown mustard (Brassica juncea (L.) Czern.) and tyfon (Brassica campestris f. biennis DC. × B. rapa L.) as green-manure on the physiological state of plants, allelopathic and biochemical characteristics of the soil in monoculture conditions of lilac (Syringa vulgaris L.). Material and methods. Seedlings of lilac were grown for 18 months under greenhouse conditions in pots with gray forest soil after monoculture of S. vulgaris. Biomass of brown mustard and tyfon was added to the soil jointly and separately in different concentrations (2.5 and 5.0 % by soil weight). The allelopathic activity, redox potential, the content of phenolic compounds and humus in soil, the concentration of the main photosynthetic pigments in leaves and seedlings growth were determined. Results. Application of green-manure contributed to increased humification, reduced soil phytotoxicity and the content of phenolic compounds, optimization of redox processes, increased chlorophyll and carotenoids concentrations in the leaves, and stimulation of seedlings growth. The formation of adaptive reactions of the pigment complex aimed at stabilizing the photosynthetic apparatus was found. Conclusion. The positive influence of brown mustard and tyfon as green-manure on the allelopathic and biochemical characteristics of the soil, as well as the physiological state of S. vulgaris plants in the conditions of the allelopathic soil sickness was established.